Structural Ecosystem, Governance, Native Court, Kudat, Matunggong SubDistrict - Rosazman Hussin; Johan Johnes; Jabil Mapjabil; Jeannet Stephen; Jurry Foo @ Jurry Bt. F. Michael; Zaini Othman; Baszley Bee Basrah Bee (Global Academic Excellence (M) Sdn Bhd (GAE), 2021)
The Sabah Native Court is a legal institution created specifically to address the application of customary law among the ethnics or indigenous peoples of Sabah. Sabah Native Court is a legal institution established by a special act known as the Native Courts Enactment 1992 amendment 1995. The purpose of this study was to identify the challenges to the governance and structural ecosystem of native courts in selected districts, specifically Kudat District and Matunggong Sub-district. This study uses qualitative methods through in-depth interviews with district heads in these two-native court. Among the study's interesting findings is the hierarchy of the organizational structure of the native court institution found in both study locations, which has differences in the number of staff appointments either at the decision-making level for district head or among native court implementers such as native chiefs and deputy native chiefs. Furthermore, the two study locations have different day-to-day governance and assignment for every entity within the native court. Questions about the benefits and drawbacks of challenges to both governance and the structural ecosystem of the native courts in both study locations were also addressed in the discussion section. Due to its importance in monitoring these challenges, this study will examine how well the native courts can resolve the concerns of each ethnic in the state compared to other judicial institutions such as the Syariah Court and Civil Court.